Identification and Mass Spectrometric Fragmentation Pathways of Chemical Components in the Traditional Chinese Medicine Formula of Jiuwei Decoction - Jia-yu ZHAO; Yue-guang LYU; Tong XIN; Qian-qian GUO; Wen-ying ZHANG; Jin-hong LI; Hong-yu XUE; Qiang MA (Zhipu Xuebao)
Traditional Chinese medicine (TCM), both a longstanding medical practice in Asia and an increasingly utilized supplement or alternative medicine in Western countries, has become a focal point within the life sciences in recent years. TCM formulations represent a cornerstone of treatment, with their chemical composition serving as the fundamental basis for their pharmacological effects. However, the intricate nature of chemical composition, low abundance of various constituents, and presence of numerous isomeric compounds, alongside interactions among different medicinal substances, render the effective separation and identification of the components in TCM herbs challenging by using traditional analytical methods. In this study, an analytical method of ultra-high-performance liquid chromatography-quadrupole/Orbitrap high-resolution mass spectrometry (UHPLC-Q/Orbitrap HRMS) was developed for identifying the chemical components in the traditional Chinese medicine formula of Jiuwei decoction. The sample pretreatment method involved ultrasonic/microwave-assisted extraction, ensuring comprehensive extraction of the active components in Jiuwei decoction. Parameters of this extraction included a microwave power at 300 W, ultrasonic power at 340 W, temperature at 45 ℃, and an extraction duration of 30 min. Subsequent to extraction, chromatographic separation was achieved using a Waters ACQUITY UPLC BEH C18 column (150 mm×2.1 mm, 1.7 µm) at 30 ℃, with an injection volume of 2 μL per run. The mobile phase consisted of water with 0.1% formic acid (A) and acetonitrile (B) at a flow rate of 0.3 mL/min. Before entering the quadrupole/Orbitrap high-resolution mass spectrometer for detection, samples underwent ionization under both positive and negative ion modes. Data acquisition was then conducted in full MS scan/data-dependent MS/MS scan (Full MS/dd-MS2) acquisition mode. Following data collection, chromatographic peak alignment and extraction were performed using the Xcalibur 4.1 software. Accurate mass information of precursor ions and fragment ions was meticulously compared with various databases, including the Orbitrap Traditional Chinese Medicine Library (OTCML), as well as other online databases such as TCMSP, ChemSpider, PubChem, PubMed, and Web of Science, in addition to a self-curated database for identification purposes. A total of 144 compounds are successfully identified, encompassing 24 flavonoids, 30 alkaloids, 12 terpenes, 23 phenylpropanoids, 26 phenols, 10 amino acids, 7 organic acids, 5 steroids, and 7 other types of compounds. Among these compounds, alkaloids such as sinomenine, phellodendrine, magnoflorine, isocorydine, and corydinematrine exhibit notably high contents and mass spectrometric responses, whereas flavonoids and saponins display comparatively lower MS responses. The herbal sources of these compounds were identified, and the fragmentation patterns of representative compounds were thoroughly analyzed. This study provides a precise identification of the chemical constituents in Jiuwei decoction, thus furnishing a robust scientific foundation for further exploration into its pharmacological effects and mechanisms of action. Moreover, this study serves as an invaluable reference for the analysis of the chemical composition of TCM formulations. Nonetheless, it is crucial to acknowledge the inherent limitations and scopes of various analytical methods and instruments. Therefore, in the pursuit of analyzing active components in TCMs, it is advisable to delve deeper into separation and identification through the utilization of diverse techniques such as nuclear magnetic resonance spectroscopy, ultraviolet/infrared spectroscopy, and capillary electrophoresis-mass spectrometry.